Hypoalbuminaemia: A Marker of Disease Severity in Acute Febrile Illnesses - K. Varghese1, Sharat M. Vijapur1,2,* and George (Recent Research in Science and Technology, 2011)
Objectives: To estimate the prevalence of hypoalbuminemia in acute febrile medical illness and whether the degree of hypoalbuminemia correlates with other markers of disease severity. Materials and methods: Acute febrile illness was defined as a febrile illness (t>101Ã‹Å¡f) of less than 7 days. The study inclusion criteria was acute febrile illnesses with at least two organ dysfunctions and excluded those with pre-existing confounding diseases. At admission, serum albumin and other markers of organ dysfunction were recorded. In recovered patients, serum albumin was repeated at their first follow up. Patients were grouped according to admission albumin levels into group 1 (<2.4gms/dl.), group II (<2.9gm/dl ≥2.5 gm/dl) and group III ( >3gm/dl). Results: Of 121 included in the study, 118 (97.5%) had hypoalbuminaemia (<3.5gm/dl) at admission with a mean admission albumin level of 2.7gm/dl. 81 patients came for follow up and repeat albumin levels could be done in 63. All showed improvement in albumin levels with a mean albumin 3.5gm/dl at follow up. Of the total of 121 patients, 35 patients (29%) were categorized as group I, 52 patients (42%) as group II, and 34 patients (29%) as group III. Group I patients compared to the other two groups showed significant differences in hypotension (54% vs 32% vs 26%, p- 0.001); need for ventilatory support (60% vs 29% vs 14%, p-.0001) and renal failure (51% vs 25% vs 17%, p-.04). Conclusions: Hypoalbuminaemia occurs frequently in acute febrile illness and appears to be a simple marker of disease severity and morbidity.